Perception of human-elephant conflict in pokkunutenna, sri lanka: a case study - Keerthanaram, T.; Lahiru pramod, J.V.G.; Riskhan, M.N.; Udaranga, H.N.S.C. (university of Jaffna, 2020)
Pokkunutenna located adjacent to Udawalawe National park, and Dahiyagala Sanctuary faces human-elephant conflict (HEC) significantly and is perceived as high in human casualties. A questionnaire survey and field assessment performed to evaluate the severity of HEC incidences, the influence of parks and sanctuary on HEC, and effective mitigatory measures for HEC in the study area. The primary data collected using a convenience sampling method. Pre-tested 42 questionnaires were used to collect data. The sample collection was systematic with five houses gap, and the sixth household was interviewed after the first household. Collected data used to obtain descriptive statistics and tested for statistical significance using the chi-square test. Results showed that the HEC has recently emerged in Pokkunutenna village and identified two main causes for this trend. Those were, villagers, adopted crop cultivation as their main livelihood support and planted food crops such as paddy, coconut, and banana that attract elephants (64%). Both the National Park and the Sanctuary provide the main entry paths for the elephants. The invasive species Lantana camara removal may reduce intruding elephants, which inhibits other plant growth; eliminating natural fodder for elephants in the Udawalawe National Park. Although clearing obstacles of electric fences may reduce the magnitude of HEC, necessary measures have to be taken to clear the Lantana camara, which is deemed a natural way of controlling HEC.
Keywords: Chi-square test; Crop depredation; Elephant attack; Key informant interview; Perception; Questionnaire survey